Stability-equivalence of bailouts and bailins with welfare consequences - Schilling, Linda (Centre for Economic Policy Research, 2024)
In a global game, I show that creditor bailins, when well-designed, can attain the exact same level of bank stability as costly creditor bailouts. This result holds for both risk-averse and risk-neutral creditors. Because bailouts are costly but do not necessarily provide a stability advantage, a ``stability-equivalent'' bailin can yield higher welfare than a bailout either if the bank is small in the economy or if the bank is large and the ex ante stability level of the bank is high. This holds even though impatient creditor types exist that have to consume early and suffer from a bailin.
https://cepr.org/publications/dp18832
Keywords: Graue Literatur; financial regulation; bank runs; global games; stability-equivalence; pol-icy effectiveness; bank resolution; haircuts; bailout; withdrawal fees; money marketmutual fund gates; suspension of convertibility